Power through prayer - Bounds, Edward M. (Edward McKendree), 1835-1913. (New Kensington, PA : Whitaker House, 2005)
"Teaches readers the importance of prayer and how to increase its effectiveness in the Christian life"--Provided by publisher.
The divine channel of power -- Our sufficiency is of God -- Man's most noble exercise -- Talking to God for men -- How to get results for God -- Great men of prayer -- "Early will I seek thee" -- The secret of power -- Power through prayers -- Under the dew of heaven -- The example of the apostles -- What God would have.
Keywords: Prayer -- Christianity